SHINE - Jung, Jessica (Electric Monkey, 2020)
For seventeen-year-old Korean American Rachel Kim, the answer is almost everything. Six years ago, she was recruited by DB Entertainment - one of Seoul’s largest K-pop labels, known for churning out some of the world’s most popular stars. The rules are simple: Train 24/7. Be perfect. Don’t date. Easy right? Not so much. As the dark scandals of an industry bent on controlling and commodifying beautiful girls begin to bubble up, Rachel wonders if she’s strong enough to be a winner, or if she’ll end up crushed . . . Especially when she begins to develop feelings for K-pop star and DB golden boy Jason Lee. It’s not just that he’s charming, sexy and ridiculously talented. He’s also the first person who really understands how badly she wants her star to rise.